Implementasi Asesmen Diagnostik Non Kognitif Pada Mata Pelajaran Pendidikan Agama Islam Kelas IV di SD Negeri - Yelna Septiana; Muhamad Fauzi; Emilia Fitri; Eva Nuryanti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
Learning and assessment are two elements that complement each other and cannot be separated. Assessment is an important part of learning to ensure the achievement of the expected educational goals. To realize effective learning and assessment, a knowledge transfer process that is able to achieve student learning goals is needed, as well as an evaluation process to find out the extent to which students have understood the material being taught. In the Independent Curriculum, non-cognitive diagnostic assessment is one of the important aspects, especially in Islamic Religious Education (PAI) subjects in elementary schools. Religious education plays a role in shaping personality and has a positive impact on the life of the nation, because its values are able to permeate various aspects of individual life. This study uses a qualitative approach with a phenomenological method that focuses on human experience. The data used consisted of primary and secondary data, with research subjects of grade IV students and PAI teachers at SD Negeri 158 Palembang. Data collection techniques include observation, interviews, and documentation, while data analysis includes collecting, reducing, presenting data, and verifying or drawing conclusions. The results of the study show that the implementation of non-cognitive diagnostic assessments in PAI subjects is divided into three stages: (1) Preparation, namely the identification of assessment instruments at the beginning of the semester; (2) Implementation, which is carried out in class at the end of class hours; and (3) Follow-up, in the form of analysis of assessment results by teachers. Supporting factors include teacher understanding, training, infrastructure, and parent involvement. However, the obstacles that arise include a lack of technical understanding, time constraints, and a lack of training and assessment tools.